The lectio ultima on Peter Lombard’s Sentences. Characteristics of the Genre Based on the Examples Preserved From the University of Cracow in the Fifteenth Century - Baran, Wojciech (Bulletin de Philosophie Médiévale, 2024)
Abstract This article deals with the lectio ultima, the last lecture on Peter Lombard’s Sentences, written by theologians from the University of Cracow in the fi fteenth century. Previous studies concerning the last question from Cracow did not recognize it as a specifi c literary genre or acknowledge its characteristics. This article will attempt to disclose these. There is a strong relationship between the lectiones ultimae and the principia on the Sentences, which, thus far, has not been described in the literature. This article characterizes the hallmarks of the lectiones ultimae which are understood as a separate literary genre and gives a catalogue of examples of this genre from the University of Cracow.